Evolved gas analysis - Fedelich, Nicolas, 1978- (Hanser Publications, 2019)
"Evolved gas analysis (EGA) describes analysis of gases or volatile components evolved from a sample undergoing thermal analysis. It is often used in direct combination with chemical analysis techniques such as gas chromatography, IR spectroscopy, or mass spectrometry, and/or with thermogravimetric analysis (TGS), i.e. measuring the change in the weight of the sample under controlled conditions. This book focuses on these so-called 'hyphenated techniques' (EGA-TGA, TGA-GC/MS, etc.), which allow a great deal of chemical information about a sample to be revealed quickly and conveniently. The methods are highly applicable to polymer/plastics samples, but also to other materials including pharmaceuticals, biomass, and various organic and inorganic compounds. Examples of applications related to all these material types are provided in this book. This book provides practical help to anyone interested in the practical aspects of EGA-TGA, including those working in testing laboratories and their clients"--Page 4 of cover